Response to “Letter to the Editor: Calcium as a confounding variable in phosphorus attribution” in As-hyperaccumulator Pteris vittata - Chun-Yan Hu; Shufen Xiao; Daniel Menezes-Blackburn; Benjamin L. Turner; Yue Cao; Chenjing Liu; Lena Q. Ma (Soil & Environmental Health)
This response addresses Dr. Zou's commentary regarding the potential role of Ca as a confounding variable in phosphorus attribution in our study. While we acknowledge the essential role of Ca in plant growth and As uptake in As-hyperaccumulator Pteris vittata, we contend that Ca did not significantly affect the results observed in this study. This is because: 1) Ca is sufficient in all treatments, 2) Ca compounds had no significant impact on As solubility, and 3) elevated Ca concentrations in the growth media did not enhance As uptake in P. vittata. Our findings suggest that P-limitation, rather than Ca supplementation, was the primary factor driving enhanced plant growth and As uptake in P. vittata. Research is ongoing to explore the roles of Ca in plant growth and As uptake by P. vittata.